Analisis Potensi dan Tantangan Pertanian Padi di Kabupaten Jember (Pendekatan Triple Helix Berbasis Content Analysis) - Hurairah Haqi Ikhlasi; Eko Hadi Cahyono; Sri Windari (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
This study examines the potential and challenges of rice farming development in Jember Regency through the Triple Helix approach, involving government, academia, and industry collaboration. Data were collected in 2024 using field observations, in-depth interviews, and questionnaires distributed to respondents, including government officials, industry representatives, academics, and farmers. The analysis focuses on variables such as production potential, technological adoption, market dynamics, and stakeholder roles in agriculture. Content analysis and descriptive statistical tools were employed to process and interpret the data. The results reveal Jember’s significant potential, including fertile land, quality seed availability, and opportunities for regional market expansion. However, limited access to subsidized fertilizers, inadequate irrigation systems, and low technological adoption hinder optimal productivity. These findings emphasize the need for targeted strategies and collaborative frameworks to address existing barriers. The study provides a foundation for future research on sustainable agricultural development and stakeholder-driven innovation.